Aplikasi Game Theory pada Pengelolaan Sumberdaya Pesisir di Selat Sebuku, Kabupaten Kotabaru, Kalimantan Selatan (The Application of Game Theory on Coastal Resources Management at Sebuku Strait, Kotabaru Regency, South Kalimantan) - Hadi, Setia; Kusumastanto, Tridoyo; Fahrudin, Achmad; Amarullah (Jurnal Aplikasi Manajemen, 2015)
Sebuku Strait has productive natural resources of renewable resources such asfishery, non-renewable resources such as coal mining and environmental services, and theexistence of marine tourism. Resources management at Sebuku Strait tends to create conflictamong stakeholders from governments, fishermen and private sectors. Therefore, a trade-offis needed in the management of Sebuku Strait area through a game theory approach oncooperative playing, and using optimum resources .This study aims to analyze the trade-offinteraction of stakeholders in the management of coastal resources to be optimal in theStrait Sebuku. In this research, game theory approach was used in cooperative game usingpareto optimum basis. Based on the research result, it was found that strategies for optimumresources management were: 1) Government and Private Sector; government should havelimited access to private sector acts in sustainable way. The government through limitedaccess strategy will gain pay off 1.271.382.286.300; whereas, private sector through sustainablestrategy will gain pay off Rp. 1.446.137.883.052; 2) Government and Fisherman;government should have limited access with fisherman act in sustainable way. The biggestpay off for each player was gained from limited access strategy implemented by governmentreach 632.579.184.900 and sustainable strategy implemented by fisherman reach659.992.193.290; 3) Private Sector and Fisherman; fisherman and private sector shouldcooperate in resources management that will gain income Rp. 945.582.505.287 peryear for private sector and Rp. 83.413.897.290 per year for fisherman.